ANALISIS KEEKONOMIAN SKEMA PSC GROSS SPLIT PADA PENGEMBANGAN LAPANGAN FR - Arinda Ristawati; Havidh Pramadika; Mustamina Maulani; Andry Prima (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Based on the Regulation of the Minister of Energy and Mineral Resources Number 52 of 2017, which later this regulation was revised into Regulation of the Minister of Energy and Mineral Resources Number 12 of 2020 the government has issued a new regulation related to the upstream oil and gas business, namely the Gross Split Production Sharing Contract scheme. In this scheme, the contractor will bear all operational costs during the development of the oil and gas field, and there is a distribution of amounts for the government and publications that are imposed before tax, the components are a base split, variable split, and progressive split. An analysis of the widespread use of the assessment components is necessary. This research will calculate the economics of the Fr field with production calculations starting in 2023. The Fr field is a field that produces oil and gas with a total oil production of 14765 Mbbl and gas of around 1,972,045 Mscf until 2036. The analysis is carried out to determine economic indicators by the calculation results for the acquisition of the Gross Split Production Sharing Contract scheme provide positive benefits for contractors in the Fr field, with a total NPV@10% of 424,010 MUSD with an IRR of 24% and a Pay Out Time of 6 years. By conducting a sensitivity analysis, the parameters that most influence the NPV and IRR in the Fr field are oil and gas production & prices.